Validation of a Scale on Pupil Wellbeing at the Elementary Schools - Kaluage, L.; Setiasih, Setiasih (International Conference on Elementary Education, 2020)
The child wellbeing at schools as an outcome had not been taken into serious consideration due to lack of measurement scale. The prime purpose of the present study was to develop and validate a scale on pupil wellbeing at elementary schools. Commencing from pooling and screening items, questionnaire consisted of 9 items were administered to 304 children at four elementary schools. Using principal axis factoring with oblique rotation, the analysis suggested that one item should be dropped and that the remaining eight items could best be represented by two factors. The obtained data were analyzed to find the underlying factors. The next step, the remaining items were distributed to 484 pupils at seven schools. A confirmatory factor analysis, using structural equation modeling, was run to test the hypothesized constructs from the previous exploration. Model fit was improved. The constructs were confirmed valid and reliable. These results led to a refined, more parsimonious version of the scale that would then use in a larger study